1991
DOI: 10.1063/1.105827
|View full text |Cite
|
Sign up to set email alerts
|

Observation of third order optical nonlinearity due to intersubband transitions in AlGaAs/GaAs superlattices

Abstract: We report the first observations of large third order optical nonlinearities in AlGaAs/GaAs superlattices due to intersubband transitions. The process is triply resonant when the first intersubband transition matches the radiation from CO2 lasers. The intersubband relaxation time has also been estimated from the dispersion of χ(3) with the laser difference frequency Δω and found to be in good agreement with other published values. The magnitude and frequency dependence of the intersubband mechanism have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 13 publications
1
53
2
Order By: Relevance
“…These dipole moments are clear evidence that the large optical nonlinearities may be obtained in semiconductor QW structures. Indeed, very large second-order nonlinear optical properties associated with ISBT such as the second harmonic generation (SHG) [3], the nonlinear optical rectification [4], and frequency down conversion [5], and third-order nonlinear optical properties such as the dc Kerr effect [6], third harmonic generation (THG) [7], and four-wave mixing [8] have been observed experimentally. Following these experimental observations, many theoretical studies related to the optical nonlinearities have also been performed [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…These dipole moments are clear evidence that the large optical nonlinearities may be obtained in semiconductor QW structures. Indeed, very large second-order nonlinear optical properties associated with ISBT such as the second harmonic generation (SHG) [3], the nonlinear optical rectification [4], and frequency down conversion [5], and third-order nonlinear optical properties such as the dc Kerr effect [6], third harmonic generation (THG) [7], and four-wave mixing [8] have been observed experimentally. Following these experimental observations, many theoretical studies related to the optical nonlinearities have also been performed [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent work, thirdorder nonlinear susceptibilities as much as five orders of magnitude greater than in bulk GaAs have been measured in coupled quantum wells by Sirtori et al [6]. In 1991, Walrod et al [7] observed a large third-order optical nonlinearity due to intersubband transitions in AlGaAs/GaAs superlattices. In 1999, Sauvage et al [8] studied third-harmonic generation in InAs/GaAs self-assembled quantum dots in both theoretical and experimental cases, and they obtained a third-harmonic-generation coefficient c ð3Þ 3w of 1:5 Â 10 À14 (m/V) 2 .…”
Section: Introductionmentioning
confidence: 96%
“…This suggests that ISB optical transitions in a QW may have very large optical nonlinearities. These nonlinear optical properties, such as electro-optic effect [10][11][12], harmonic generation [12][13][14][15][16][17][18][19][20], optical absorption effect [21][22][23][24][25][26] and refractive index changes [10,[24][25][26][27], have the potential for device applications.…”
Section: Introductionmentioning
confidence: 99%